Early diagnosis of subclinical peripheral polyneuropathy in prediabetes and obesity - Nargizakhon, Kodirova; Jurayeva, Aziza (Uzbekistan Open Conference, 2026)
Subclinical peripheral polyneuropathy in patients with prediabetes and obesity often remains undetected due to the limited sensitivity of routine diagnostic methods. Early identification of small fiber damage is important for preventing the progression of metabolic neuropathy and type 2 diabetes mellitus. The aim of the study was to evaluate the diagnostic significance of modern instrumental methods for detecting subclinical peripheral polyneuropathy in patients with prediabetes and obesity. A prospective comparative clinical study was conducted in 2024–2025 and included 120 patients aged 35–60 years. The main group consisted of 80 patients with prediabetes and obesity (BMI ≥30 kg/m²), while the control group included 40 healthy individuals without carbohydrate metabolism disorders. All participants underwent electroneuromyography, quantitative sensory testing (QST), and skin biopsy with immunohistochemical assessment of intraepidermal nerve fiber density using the PGP 9.5 marker. In the main group, serum levels of leptin, adiponectin, IL-6, and TNF-α were additionally measured by ELISA. Subclinical signs of peripheral polyneuropathy were detected in 41% of patients in the main group. According to electroneuromyography, reduced nerve conduction velocity was observed in 20% of cases, impaired temperature sensitivity by QST in 34%, and decreased intraepidermal nerve fiber density in 39% of patients. Skin biopsy demonstrated the highest diagnostic accuracy (AUC=0.87), followed by QST (AUC=0.81) and electroneuromyography (AUC=0.69). An inverse correlation was found between the leptin/adiponectin ratio and nerve fiber density (r=–0.44; p
Keywords: Prediabetes; Obesity; Peripheral Polyneuropathy; Small Fiber Neuropathy; Early Diagnosis